A global checklist of the parasites of the harbor porpoise Phocoena phocoena, a critically-endangered species, including new findings from the Baltic Sea. (August 2021) - Dzido, Joanna; Rolbiecki, Leszek; Izdebska, Joanna N.; Rokicki, Jerzy; Kuczkowski, Tytus; Pawliczka, Iwona
Abstract: The common harbor porpoise is a widely-distributed marine mammal with three known subspecies, including P. phocoena phocoena, with a clearly distinct and critically endangered (CR) subpopulation from the Baltic Sea (Baltic Proper). As part of an assessment of the condition and health threats of these mammals, it is important to conduct parasitological monitoring. The aim of the study was therefore to compare the data on porpoise parasitofauna from this subpopulation with those on porpoises from other areas. The study included 37 individuals from 1995 to 2019; eight species of parasites were found (prevalence 83.8%, mean intensity 724.2, range 2–3940), with a predominance of lung nematodes – Stenurus minor (94.7%), Torynurus convolutus (69.4%), Pseudalius inflexus (63.8%), Halocercus invaginatus (22.2%); the highest intensity was recorded for S. minor (989, 53–2928). Two species of Anisakidae ( Anisakis simplex – 33.3%, Contracaecum sp. – 20.0%) were found in the digestive tracts, which were a new record for this population. The fluke Campula oblonga was found in the livers of 31.3% of porpoises. The tapeworm Diphylobothrium stemmacephalum was also recorded in the intestine of one individual; this is typical for these hosts, but previously undetected in the Baltic subpopulation. Parasites coexisted in numerous hosts, constituting a heavy burden for them. The obtained data were compared with those from the P. phocoena parasitofauna from other regions, based on a compiled checklist (1809–2021) including all species of porpoise parasites (55 taxa). Compared to the worldwide porpoise parasitofauna checklist, the number of parasites found in the nominative subspecies (Baltic Proper subpopulation) is small: including only 10 taxa (eight in the current study). These species are typical of porpoises and usually the most common; however, the level of infection of Baltic porpoises (intensity and total parasite load) is very high, which can undoubtedly have a negative impact on their condition and overall health. Graphical abstract: Image 1 Highlights: The common harbor porpoise is a widely-distributed marine mammal. The harbor porpoise population of the Baltic Sea is classified as Critically Endangered (CR). The worldwide porpoise parasitofauna checklist the list consists of 55 taxa, including 36 identified to the species rank. In the small size of the Baltic subpopulation, only 10 species of parasites were found, but with very high burdens of infection. Parasites showing a high level (intensity) of infection, especially lung nematodes, can pose a significant threat to the condition, health and survival of porpoises.